Značilnosti krajše proze slovenskih književnic - Borovnik, Silvija (Slavia Centralis, 2020)
Characteristics of Slovenian Female Literary Writer’s Short Prose This article discusses the characteristics of Slovenian female writers’ short prose from its beginnings (at the turn of the 19th to 20th century) to the present. The selection of authors and literary texts alerts us to the thematic and linguistic novelties and peculiarities of their literature. The selection also exhibits lacunæ in research and knowledge of the aforementioned literature.